Pengaruh Faktor Pribadi Dan Psikologi Terhadap Keputusan Berlangganan TV Kabel Transvision Di Kelurahan Tongkaina - Harun, Sharas Devi; Tamengkel, Lucky F.; Punuindoong, Aneke Y. (JURNAL ADMINISTRASI BISNIS (JAB), 2019)
This study aims to determine: (1) the influence of personal factors on the decision to subscribe to Transvision cable TV, (2) the influence of psychological factors on the decision to subscribe to Transvision cable TV, and (3) the influence of personal factors and psychological factors on the decision to subscribe to Transvision cable TV. This study uses a quantitative approach by collecting data through literature and questionnaire methods. This study also uses saturated sampling techniques or sampling techniques if all populations are sampled. The sample in this study were 98 Transvision cable TV customers who included the Tongkaina urban community in Manado. Data collection techniques use questionnaires that have been tested for validity and reliability. The data analysis technique used to answer the hypothesis is multiple regression. The results of this study indicate that: (1) Personal factors have a positive effect on subscription decisions, as evidenced by the value of t count which is 2.363 with a significance value of 0.020, smaller than 0.05 and the regression coefficient has a positive value of 0.143. (2) Psychological factors have a positive effect on subscription decisions, as evidenced by the value of t count of 2.114 with a significance value of 0.037, smaller than 0.05 and the regression coefficient has a positive value of 0.145, and (3) Personal factors and psychological factors have a positive effect on subscription decision, evidenced by the results of F count of 5.236 with a significance of 0.007. The R square value or coefficient of 0.099 shows that the ability of the independent variable in explaining the variation of the dependent variable is 9.90%, while the remaining 90.10% is explained by other variables outside the study.